Influence of methadone on clopidogrel in addicts on methadone maintenance therapy - Ferigol Fallah; Abolhasan Hamidikenari; Seyed Navid Sajadi; Seyed Rohollah Sajadi; Mohammad Reza Shiran (Caspian Journal of Internal Medicine, 2016)
Background: Clopidogrel is a prodrug that converts in the liver to an active thiol metabolite, which irreversibly inhibits the platelet P2Y12 adenosine diphosphate receptor. It seems that methadone as CYP2C19 inhibitor affects ticlopidine activity in vivo. This study aimed to test the ability of methadone in changing ticlopidine pharmacokinetics.